Socialization of Crop-Livestock Integration System to Increase Farmer-Livestock Income in the Framework of Community Empowerment - Nurul Komariyatin; Nanang Yusroni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Food security is a strategic concern for emerging nations. A crop-livestock integration system must generally be put in place if the Indonesian people are to attain food security, independence, and sovereignty. One of the most advanced agricultural systems available today is the integrated crop-livestock system. One of the agricultural systems that promotes the expansion of the farm industry in rural regions is the crop-livestock integration system. One of the communities in Jepara with significant potential for agricultural and animal husbandry is Karangrandu Village, located in the Pecangaan District of the Jepara Regency. The crop-livestock integration system is a particularly useful tool since many farmer groups have not yet improved the transformation of food crop waste into animal feed and livestock manure into organic fertilizer.